2018
DOI: 10.2147/ptt.s169389
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genital psoriasis on quality of life: a systematic review

Abstract: Psoriasis is a chronic immune-mediated inflammatory disease with significant medical and psychological comorbidities. In addition to having increased cardiovascular risk and mortality, psoriasis patients are more likely to be depressed, anxious, and endorse suicidal ideation than the general population. These patients often have low self-esteem and feel stigmatized due to their skin disease, which can prevent them from pursuing relationships, dating, and attending social activities. Up to 63% of adult psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 43 publications
(63 reference statements)
3
47
0
Order By: Relevance
“…They also reported more QoL impairments in general (DLQI) and in sexual functioning (DLQI-i9), as well as increased need to improve sex life (PNQ-i17). This general overview of results seems foreseeable and in accordance to previous literature [ 6 9 ], as genital psoriasis has been strongly associated with increased severity and with an increased number of previous systemic treatments (which can be considered a surrogate measure for severity over time) [ 30 ]. In addition, in-depth analyses considering patients’ gender and methodological constraints of PRO showed that the results were much more complex than the simple relationship between anogenital psoriasis and loss of QoL.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…They also reported more QoL impairments in general (DLQI) and in sexual functioning (DLQI-i9), as well as increased need to improve sex life (PNQ-i17). This general overview of results seems foreseeable and in accordance to previous literature [ 6 9 ], as genital psoriasis has been strongly associated with increased severity and with an increased number of previous systemic treatments (which can be considered a surrogate measure for severity over time) [ 30 ]. In addition, in-depth analyses considering patients’ gender and methodological constraints of PRO showed that the results were much more complex than the simple relationship between anogenital psoriasis and loss of QoL.…”
Section: Discussionsupporting
confidence: 87%
“…The present study was conducted to gain insight into the overall and sex-related QoL impairments, patient needs and treatment benefits in patients affected by anogenital psoriasis, compared to a control group of patients with psoriasis not affecting the anal or genital body regions. There is a remarkable lack of literature on disease burden in the presence of psoriasis lesions in the anal/genital skin, particularly studies relying on PRO [ 6 ]. This study has several strengths and provides innovative analyses and results, with relevant contributions for further research and clinical practice, namely: (1) the inclusion of both anal and genital psoriasis; (2) the use of a high-resolution grid scheme on the topology of psoriasis; (3) the analysis of overall and sex-related patient-defined needs and benefits from treatment in different groups in relation to gender and anogenital involvement; and (4) the examination of MR and NNR rates to sex-related items in widely used questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psoriasis is a chronic disease characterized by erythematous, scaly, and hyperkeratotic plaques that can extend all over the skin. Psoriasis is widely recognized to diminish quality of life, especially when sensitive areas, such as genitals, are involved [1]. Basic research and several clinical trials have suggested a dominant role of interleukin 17A (IL-17A) in the pathogenesis of psoriasis [2].…”
Section: Mild Therapeutic Response Of Alopecia Areata During Treatmenmentioning
confidence: 99%